Multiple mini interview (MMI) for general practice training selection in Australia: interviewers’ motivation - Burgess, Annette (BMC Med Educ, 2018)
BACKGROUND: Multiple Mini Interviews (MMIs) are being used by a growing number of postgraduate training programs and medical schools as their interview process for selection entry. The Australian General Practice and Training (AGPT) used a National Assessment Centre (NAC) approach to selection into General Practice (GP) Training, which include MMIs. Interviewing is a resource intensive process, and implementation of the MMI requires a large number of interviewers, with a number of candidates being interviewed simultaneously. In 2015, 308 interviewers participated in the MMI process – a decrease from 340 interviewers in 2014, and 310 in 2013. At the same time, the number of applicants has steadily increased, with 1930 applications received in 2013; 2254 in 2014; and 2360 in 2015. This has raised concerns regarding the increasing recruitment needs, and the need to retain interviewers for subsequent years of MMIs. In order to investigate interviewers’ reasons for participating in MMIs, we utilised self-determination theory (SDT) to consider interviewers’ motivation to take part in MMIs at national selection centres. METHODS: In 2015, 308 interviewers were recruited from 17 Regional Training Providers (RTPs) to participate in the MMI process at one of 15 NACs. For this study, a convenience sample of NAC sites was used. Forty interviewers were interviewed (n = 40; 40/308 = 13%) from five NACs. Framework analysis was used to code and categorise data into themes. RESULTS: Interviewers’ motivation to take part as interviewers were largely related to their sense of duty, their desire to contribute their expertise to the process, and their desire to have input into selection of GP Registrars; a sense of duty to their profession; and an opportunity to meet with colleagues and future trainees. Interviewers also highlighted factors hindering motivation, which sometimes included the large number of candidates seen in one day. CONCLUSION: Interviewers’ motivation for contributing to the MMIs was largely related to their desire to contribute to their profession, and ultimately improve future patient care. Interviewers recognised the importance of interviewing, and felt their individual roles made a crucial contribution to the profession of general practice. Good administration and leadership at each NAC is needed. By gaining an understanding of interviewers’ motivation, and enhancing this, engagement and retention of interviewers may be increased. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12909-018-1128-z) contains supplementary material, which is available to authorized users.